1994
DOI: 10.1037/0033-2909.116.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Self-disclosure and liking: A meta-analytic review.

Abstract: Self-disclosure plays a central role in the development and maintenance of relationships. One way that researchers have explored these processes is by studying the links between self-disclosure and liking. Using meta-analytic procedures, the present work sought to clarify and review this literature by evaluating the evidence for 3 distinct disclosure-liking effects. Significant disclosure-liking relations were found for each effect: (a) People who engage in intimate disclosures tend to be liked more than peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
941
3
14

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,249 publications
(1,023 citation statements)
references
References 113 publications
37
941
3
14
Order By: Relevance
“…Therefore, as we learn more about a person, we tend to rely more on that new information and less on stereotypes. Similarly, disclosure research has shown that sharing personal information with others can foster intimacy, liking, and trust (Collins & Miller, 1994;Manne et al, 2004;Turner, Hewstone, & Voci, 2007). Therefore, because relationships are constantly changing over time as people have new experiences with and learn more about each other, examining the extent to which an individual perceives, witnesses, or engages in subtle discrimination with a particular person at a single snapshot in time is insufficient to fully understanding the experience and consequences of subtle discrimination within a particular relationship.…”
Section: The Dynamic Nature Of Relationshipsmentioning
confidence: 99%
“…Therefore, as we learn more about a person, we tend to rely more on that new information and less on stereotypes. Similarly, disclosure research has shown that sharing personal information with others can foster intimacy, liking, and trust (Collins & Miller, 1994;Manne et al, 2004;Turner, Hewstone, & Voci, 2007). Therefore, because relationships are constantly changing over time as people have new experiences with and learn more about each other, examining the extent to which an individual perceives, witnesses, or engages in subtle discrimination with a particular person at a single snapshot in time is insufficient to fully understanding the experience and consequences of subtle discrimination within a particular relationship.…”
Section: The Dynamic Nature Of Relationshipsmentioning
confidence: 99%
“…Self‐disclosure is integral to the formation and maintenance of positive interpersonal relationships (Altman & Taylor, 1973; Reis & Shaver, 1988). Receiving intimate disclosure increases interpersonal trust and liking of the discloser (Collins & Miller, 1994) and is likely to be reciprocated, leading to mutual interpersonal attraction (Laurenceau, Barrett, & Rovine, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…We suggest that this association rests at least in part on the experience of perceived partner exclusion, or the perception that one is separated from and excluded by one's partner. Because concealment is a social process, we propose that it signals avoidance, separation, and rejection; that is, a partner who is perceived to conceal information is assumed to distance himself or herself from the person and to exclude the person, whereas a partner who is perceived to be open and not conceal information is assumed to be close and intimate and to like the person (e.g., Collins & Miller, 1994;Finkenauer, Engels, Branje, & Meeus, 2004). The perception of concealment conveys separation, distance, and exclusion, whereas the perception of disclosure conveys closeness, intimacy, and sharing.…”
Section: The Perception Of Concealment As a Signal Of Exclusionmentioning
confidence: 99%